Analisis Kekerasan Simbolik dalam Penetapan Kebijakan Pembatasan Jam Kegiatan Malam di Lingkungan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin: Analysis of Symbolic Violence in Determining the Policy of Limiting Night Activity Hours in the Faculty of Social and Political Sciences, Hasanuddin University - Wijangga, Putu; Ramadhan, Syahril; Haris, Nirmala; Kemal, A. Muh.; Reza, Muh.; Tanggang, Alfira; Wulandari, Sri; Hamsyah; Aprilia S, Zahra; Chadid Amin Noor, Khairunnisa; Ishak; Octaviani, Mely (Department of Sociology Faculty of Social and Political Sciences, 2024)
This research aims to find out how the portrait of symbolic violence in determining the policy of limiting night activity hours in the Faculty of Social and Political Sciences, Hasanuddin University. Data collection in this study was carried out in March 2024 using a qualitative research approach. The informants in this study were determined using purposive sampling technique where the informants interviewed must meet certain criteria. The results showed that there are several forms of symbolic violence from the establishment of this policy, namely 1). the occurrence of restrictions on public access for students in this case campus facilities, 2). the occurrence of security guard intimidation in this case the expulsion of students who carry out activities beyond the specified hours, 3). the non-involvement of students in policy making and 4). restrictions on student movement through regulations/policies. In addition, the success of the bureaucracy in determining this policy is inseparable from several factors such as ownership of capital, both social, economic and symbolic capital owned by the bureaucracy, then position and rank become the power of the bureaucracy to determine this policy and habitus in this case the understanding of students.